Amentotaxus (Taxaceaf)-A Rare Gymnosperm from Arunachal Pradesh - Haridasan, K. (Indian Forester, 1988)
The anatomical studies on Bauhinia retusa Ham. have been carried out with particular reference to gum exudation. The observations indicate that like other gum yielding trees gum canals either normal or traumatle or gum cysts are not present in this species but the vessels near the cambium are filled with gum due to wounding and the gum exudes from these vessels in tears. The vessels formed during tbe year of rest are free from gummy deposits.